The Modernization of Pesantren Education Based on Nurcholis Madjid’s Perspectives - Mustofa, Akhmad Miftakhul (Tadibia Islamika: Journal of Holistic Islamic Education, 2021)
This study aims to delve into the world of Islamic boarding schools from the perspective of Nurcholish Madjid. It posits that pesantren is not solely an institution dedicated to religious studies, but rather, it must adapt to contemporary challenges, particularly in the digital age, necessitating a process of modernization. The rejuvenation of pesantren has been significantly influenced by the ideas of various intellectuals, among whom Nurcholish Madjid holds a prominent place. This research adopts a library-based methodology, employing a historical-philosophical approach. The findings of this study are as follows: (1) The organizational structure of Islamic boarding schools has evolved over time, transitioning from a single leadership model to an institutional framework. (2) The curriculum within Islamic boarding schools is undergoing modernization, shifting from traditional methods like sorogan, lalaran, bandongan, and halaqoh towards a more hierarchical approach. Additionally, the pesantren curriculum now incorporates vocational training and skills development. (3) The role of pesantren has expanded beyond its original functions of transmitting Islamic knowledge, preserving Islamic traditions, and nurturing scholars. It has undergone a process of refunctionalization, now encompassing social and economic roles, allowing it to adapt and thrive in the contemporary era.